How Do Political Factors Shape the Bank Risk-Sovereign Risk Nexus in Emerging Markets? - Stefan Eichler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper studies the role of conditioning political factors for determining the impact of banking crises on sovereign bond yield spreads for a sample of 33 emerging economies in the period 1995-2010. Accounting for the endogenous nature of banking crisis outbreaks, I find that sovereign bond yield spreads increase, on average, by 13 to 17 percentage points during banking crisis episodes. I find that the adverse impact of banking crises on sovereign solvency is less pronounced (or even insignificant) for countries run by powerful and effective governments, low levels of public debt, and a high degree of political stability.
Keywords: G01; G21; G12; 330